Bio-inspired design of hierarchical PDMS microstructures with tunable adhesive superhydrophobicity. Issue 14 (16th March 2015) - Zhang, Enshuang; Wang, Youshan; Lv, Tong; Li, Li; Cheng, Zhongjun; Liu, Yuyan
Abstract : A series of tunable adhesive super-hydrophobic PDMS films were reported by directly designing similar microstructures with those on lotus leaves and rose petals. Abstract : In this paper, bio-inspired PDMS films with different hierarchical microstructures were designed and tunable adhesive super-hydrophobicity was achieved on these films. The adhesive forces between a water droplet and the PDMS film can be adjusted from extremely low (about 8.3 μN) to very high (about 57 μN), and the tunable effect can be ascribed to different wetting states for the water droplets that result from different microstructures on the films. Noticeably, the obtained super-hydrophobic surfaces are acid/alkali-resisting, and water droplets with different pH values have similar contact angles and adhesive forces on the same surface. Finally, the application of the obtained surfaces for microdroplet transportation and self-cleaning are also discussed. The results reported herein provide a new method to obtain super-hydrophobic surfaces with controlled adhesion, and significantly improve our understanding of the relationship between surface adhesion, surface microstructures and the fabrication principle of tunable adhesive super-hydrophobic surfaces.